2022
DOI: 10.3390/su14031531
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Capabilities to Achieve Corporate Sustainability: A Roadmap to Sustained Competitive Advantage

Abstract: Dynamic capabilities and sustainability practices have become the center of attention for companies globally, but there is still a debate on how organizations can successfully develop dynamic capabilities and achieve sustainability for competitive advantage. This paper discusses the outcomes of a comprehensive systematic literature review (SLR) following the PRISMA guidelines and employs dynamic capabilities theory to suggest that strategic routines and competencies, integrated value chains, sustainability-ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 52 publications
2
36
0
1
Order By: Relevance
“…Meanwhile, there may exist a close association between GVC and GDC . Specifically, many studies have suggested that value co‐creation improves the dynamic capability of enterprises (Bari et al, 2022; Fang, 2008; Preikschas et al, 2017; Siaw & Sarpong, 2021). Firstly, value co‐creation facilitates organizational innovation and develops dynamic capability through cooperation with stakeholders (Bari et al, 2022; Bocken & Geradts, 2020; Cezarino et al, 2019; Kumar et al, 2018).…”
Section: Literature Review and Hypotheses Developmetmentioning
confidence: 99%
“…Meanwhile, there may exist a close association between GVC and GDC . Specifically, many studies have suggested that value co‐creation improves the dynamic capability of enterprises (Bari et al, 2022; Fang, 2008; Preikschas et al, 2017; Siaw & Sarpong, 2021). Firstly, value co‐creation facilitates organizational innovation and develops dynamic capability through cooperation with stakeholders (Bari et al, 2022; Bocken & Geradts, 2020; Cezarino et al, 2019; Kumar et al, 2018).…”
Section: Literature Review and Hypotheses Developmetmentioning
confidence: 99%
“…As an important part of the sustainable development strategy of enterprises, the sustainable competitiveness of enterprises is not only a strong support for the development of enterprises, but also the only way for the sustainable development of enterprises. erefore, sustainable competitive advantage has always been the topic of concern of enterprise strategy theory [6,7]. Porter [8] first mentioned sustainable competitive advantage when discussing the company's long-term competitive advantage to obtain low cost or differentiation, and pointed out that the sustainable competitive advantage of an enterprise comes from the value it creates for customers that exceeds its cost, which ultimately depends on the value it can create for customers.…”
Section: Sustainable Competitive Advantage and Customer Perceived Valuementioning
confidence: 99%
“…While the objective is to deliberate on the terms under which the resources of this company can be under a sustained competitive advantage, the company is seen to have a sustainable competitive advantage when it meets two conditions [62][63]. First condition is when the firm executes a value creating strategy which is not simultaneously being implemented by any current or potential competitors; and secondly, when other firms are unable to duplicate the benefits on this strategy [64].…”
Section: Model For Sustained Competitive Advantagementioning
confidence: 99%